People's Republic of China-Hong Kong Special Administrative Region : Selected Issues. (IMF Staff Country Reports; Country Report ;, 2018)
This Selected Issues paper examines medium-term fiscal prospects and policy recommendations for Hong Kong Special Administrative Region (SAR). Hong Kong SAR's fiscal framework has worked well over the last 20 years but challenges have emerged that will strain the fiscal position in the medium to long term. Consequently, while fiscal space is ample currently, it could become gradually constrained over time. The fiscal rule should be implemented flexibly and revenue mobilization needs to be considered down the road. On the expenditure side, containment will be hard, given rapid aging and still high inequality. The challenge will be to maintain investment and boost land supply while increasing social spending to guarantee that those who need support are effectively protected.